An insight of different classes of RNA-based therapeutic, nanodelivery and clinical status: Current landscape - Srijan Chatterjee; Manojit Bhattacharya; Sang-Soo Lee; Chiranjib Chakraborty (Current Research in Biotechnology, 2023)
The first RNA therapeutic molecule, Fomivirsen, was approved for a clinic in 1998 as an antisense oligonucleotide therapeutic. Twenty-four years later, we found that more than a dozen RNA therapeutics had received approval and entered the clinic. In this direction, the review article illustrated the journey of different classes of RNA-based therapeutics from bench to clinic. The article extensively describes a critical insight into the advancements and clinical status of nanoparticle-based delivery for various classes of RNA-based therapeutics, biopharma companies' role, and the different classes of RNA-based therapeutics. It also highlights the diverse nanoparticle formulations, including lipid-based, polymeric, and inorganic nanoparticles, emphasizing their distinct characteristics and benefits in delivering RNA-based therapeutics with precision. Additionally, the review emphasizes the significance of surface functionalization and targeting ligands in improving the delivery efficiency and site-specificity of nanoparticles for therapeutic applications. The article explores diverse classes of therapeutics, including antisense oligonucleotides, guide RNAs, siRNAs, aptamers, ribozymes, miRNAs, and mRNAs, showcasing their efficacy in clinical settings. Chemical modifications in the therapeutics' structure are also highlighted as a strategy to overcome obstacles. The success of FDA-approved RNA-based therapeutics offers hope for future clinical advancements against a range of diseases.